2020
DOI: 10.1002/cti2.1151
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the optimal donor for natural killer cell adoptive therapy to treat paediatric B‐ and T‐cell acute lymphoblastic leukaemia

Abstract: Objectives. Natural killer (NK) cells are an attractive source of cells for an 'off the shelf' cellular therapy because of their innate capacity to target malignant cells, and ability to be transferred between donors and patients. However, since not all NK cells are equally effective at targeting cancer, selecting the right donor for cellular therapy is critical for the success of the treatment. Recently, cellular therapies utilising NK cells from cytomegalovirus (CMV)seropositive donors have been explored. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…This suggests that while NKG2C marks adaptive NK cells, its contribution to the recognition and elimination of cancer cells remains unclear. In support of this we have recently demonstrated that while NKG2C + adaptive NK cells were associated with increased effector function against B cell ALL, NKG2C recognition of HLA-E was not involved in this increased function [ 100 ]. There is also rationale to exploit the enhanced ADCC potential of adaptive NK cells to generate improved responses against cancer when using monoclonal, bispecific and trispecific antibodies [ 96 ].…”
Section: Current Status On the Role Of Adaptive Nk Cells In Cancermentioning
confidence: 71%
“…This suggests that while NKG2C marks adaptive NK cells, its contribution to the recognition and elimination of cancer cells remains unclear. In support of this we have recently demonstrated that while NKG2C + adaptive NK cells were associated with increased effector function against B cell ALL, NKG2C recognition of HLA-E was not involved in this increased function [ 100 ]. There is also rationale to exploit the enhanced ADCC potential of adaptive NK cells to generate improved responses against cancer when using monoclonal, bispecific and trispecific antibodies [ 96 ].…”
Section: Current Status On the Role Of Adaptive Nk Cells In Cancermentioning
confidence: 71%
“…Despite the existence of a plethora of strategies to enhance the cytotoxicity and persistence of therapeutic NK cells in vivo, the initial selection of highly functional cells with strong innate potency is essential for the widespread success of NK cell therapies. Over the past decade it has become increasingly evident that not all NK cells have the same baseline capacity to eradicate leukaemic cells (33)(34)(35)(36)(37). In addition to the functional differences between traditional NK cell subsets (33)(34)(35), variability also exists in the functional capacity of NK cells derived from different individuals (36,37).…”
Section: Donor Selection For Improved Nk Cell Therapiesmentioning
confidence: 99%
“…Over the past decade it has become increasingly evident that not all NK cells have the same baseline capacity to eradicate leukaemic cells (33)(34)(35)(36)(37). In addition to the functional differences between traditional NK cell subsets (33)(34)(35), variability also exists in the functional capacity of NK cells derived from different individuals (36,37). However, relatively little attention has been given to optimizing the particular subset or donor from which these cells are derived.…”
Section: Donor Selection For Improved Nk Cell Therapiesmentioning
confidence: 99%
See 2 more Smart Citations